Beyond transformations: Zooming in on agricultural digitalization and the changing social practices of rural farming in Northern Ghana, West Africa - Abdulai, Abdul-Rahim; Gibson, Ryan; Fraser, Evan D.G. (Elsevier, 2023)
Digitalization of agriculture (DA) has emerged as a powerful rural transformative force. However, the dynamics of how digitalization is changing smallholder farming practices at the heart of rural life remain underexplored. Here, we employ a mixed-method approach (1565 survey respondents, 16 focus group discussions, and 22 interviews) to examine farmers' experiences with digital agriculture services in Northern Ghana through a social practice theory (SPT) lens. We found that farmers perceive digitalization as transitioning their everyday activities across the farming spectrum, including decisions and activities related to season planning, planting, husbandry, harvesting, post-harvest management, and sales. Notably, 1) new materials of phones and digital platforms redefine farmers’ knowledge and competencies, ultimately 2) temporary re-patterning their routines and rhythms. Therefore, we argue that, beyond the contested claims of digital transformations, a pertinent dimension of DA and rural social change is the transitions in the everyday practices of farmers and rural living. Our paper, as we know, is among the early attempts to theoretically and empirically examine agriculture digitalization through an explicit practice lens, and more so in the context of African smallholder systems. We contribute to the scholarship on DA and rural change by (re)framing the dynamics of the phenomenon through everyday practices. By this approach we aim to steer the DA discourse and policy from the optimistic rural transformations towards the often-overlooked yet critical gradual changes and transitions in the day-to-day life of farmers.